Editorial: Integrated biosensors towards clinical and point-of-care diagnostics - Chandra, Pranjal; Morales-Narvaez, Eden; Dincer, Can (Frontiers Media S.A., 2022)
Biosensing devices such as lateral flow assays, blood glucose test strips or wearable continuous glucose monitoring systems have had a great impact on healthcare for more than half a century and have already improved our living standards. In particular, biosensors allow us to measure clinically relevant biomarkers from various sample matrices (including whole blood, plasma, saliva, or urine) in a fast, cost-effective, and user-friendly manner. Hence, biosensing technologies can provide vital information related to the propensity for illness or the status of a disease, or its treatment monitoring. However, there are still some challenges, especially regarding the sample Research Topic and preparation as well as the biosensing performance of diagnostic devices (Ates et al., 2021). To further assess the potential of this technology, researchers are pushing forward the frontiers of integrated biosensors, combining the sample Research Topic, preparation, analysis, and data evaluation, to create “sample-in-answer-out” diagnostic devices. Such integrated solutions for biosensing could enable real-time, highly sensitive, and selective quantification of various biomolecules within clinically relevant body fluids in a smart, sustainable, interoperable, and portable manner. This Research Topic gathers innovative approaches for integrated biosensing systems conceived from colleagues located in diverse parts of the world, including Australia, China, Denmark, Taiwan, the United Kingdom, and the United States. Several clinically relevant agents are targeted, including respiratory viruses (Fan et al.), interleukin-6 (a biomarker of inflammatory associated diseases) (Rahbar et al.), biomarkers related to gastric cancer (Liu et al.), dengue serotypes (Moser et al.), SARS-CoV-2 virus (Lin et al.; Ngoc et al.), and carbohydrate antigen 50 (a non–organ-specific tumor biomarker for screening several cancers) (Liu et al.). All of them were presented with (potential) clinical applications at the point-of-care. In particular: Fan et al. integrated recombinase aided amplification (a novel isothermal amplification method targeting the genetic material of various pathogens) and quantitative polymerase chain reaction (qPCR) in order to detect respiratory viruses (ADV3 and ADV7). A conventional qPCR
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Point-of-care testing; On-site detection; Health 4.0; Microfluidics; Non-invasive diagnostics; Sample preparation